Emotion regulation as a mechanism of mindfulness in individual cognitive-behavioral therapy for depression and anxiety disorders - Prüßner, Luise; Timm, Christina; Kalmar, Julia; Bents, Hinrich; Barnow, Sven; Mander, Johannes (Depression and anxiety, 2024)
Background. The global prevalence of depression and anxiety disorders underscores the need for a more profound comprehension of effective treatments. Mindfulness has shown promise in enhancing treatment outcomes and preventing relapse in these conditions, but the underlying mechanisms remain poorly understood. Methods. This study examined the role of emotion regulation as a mediator in the relationship between changes in mindfulness and the reduction of depression and anxiety symptoms during individual cognitive-behavioral therapy (CBT). We tracked longitudinal changes in mindfulness, emotion regulation, depression, and anxiety at baseline (pre), early treatment (session 5), midtreatment (session 15), and posttreatment (session 25) in 162 patients with depression and anxiety disorders. Further, we examined whether the effects of mindfulness on emotion regulation could be enhanced by introducing a brief mindfulness intervention at the beginning of each CBT session, as compared to progressive muscle relaxation and individual psychotherapy without any standardized session-introducing interventions. Results. Multilevel structural equation modeling indicated that decreases in rumination and increases in reappraisal and acceptance mediated the relationship between mindfulness and reductions in depressive symptoms. In contrast, reductions in avoidance explained the association between mindfulness and changes in anxiety symptoms. These links remained unchanged when adding a mindfulness intervention into individual CBT. Conclusion. Results support emotion regulatory properties of mindfulness and highlight distinct pathways of symptom reduction in depression and anxiety. These findings have important implications for understanding the mechanisms of mindfulness and tailoring treatment to individual patient needs. This trial is registered with NTC02270073.